Respuesta :
Answer:
1) [tex]p=3[/tex]
2)[tex]t=-7[/tex]
3)[tex]x=15[/tex]
4) [tex]x=7[/tex]
Step-by-step explanation:
1) Apply distributive property:
[tex]2(p+ 5) = 16\\2p+10=16[/tex]
Subtract 10 from both sides of the equation and then divide both sides by 2:
[tex]2p+10-10=16-10\\\frac{2p}{2}=\frac{6}{2}\\p=3[/tex]
2) Apply distributive property:
[tex]-3(t + 1) = 18\\-3t -3= 18[/tex]
Add 3 to both sides of the equation and then divide both sides by -3:
[tex]-3t -3+3= 18+3\\\frac{-3t}{-3}=\frac{21}{-3}\\t=-7[/tex]
3) Apply distributive property:
[tex]-\frac{2}{5}(x+10)=-10\\\\-\frac{2}{5}x-4=-10[/tex]
Add 4 to both sides of the equation:
[tex]-\frac{2}{5}x-4+4=-10+4\\\\-\frac{2}{5}x=-6[/tex]
Multiply both sides by [tex]-\frac{5}{2}[/tex]:
[tex](-\frac{2}{5}x)(-\frac{5}{2}) =-6(-\frac{5}{2})\\\\x=15[/tex]
4) Apply distributive property:
[tex]\frac{2}{3}(x-10)=-2\\\\\frac{2}{3}x-\frac{20}{3}=-2[/tex]
Add [tex]\frac{20}{3}[/tex] to both sides of the equation:
[tex]\frac{2}{3}x-\frac{20}{3}+\frac{20}{3}=-2+\frac{20}{3}\\\\\frac{2}{3}x=\frac{14}{3}[/tex]
Multiply both sides by [tex]\frac{3}{2}[/tex]:
[tex](\frac{2}{3}x)(\frac{3}{2})=(\frac{14}{3})(\frac{3}{2})\\\\x=7[/tex]
Hello!
The answers are:
1 [tex]p=3[/tex]
2 [tex]x=-7[/tex]
3 [tex]x=35[/tex]
4 [tex]x=7[/tex]
Why?
To know the solution of the problems, we need to isolate each variable.
Remember that:
- If we have an equality: if the number is part of a product , and if you need to move it to the other side of the equality, the same number will be dividing the factors of the side.
- If we have an equality: if the number is subtracting (negative sign), and if you need to move it to the other side of the equality, its sign changes to positive.
- If we have an equality: if the number is adding (positive sign), and if you need to move it to the other side of the equality, its sign changes to negative.
- The distributive property states that:
[tex]a(b+c)=ab+ac[/tex]
So,
1 - Solving for p
[tex]2(p+5)=16\\2p+10=16\\2p=16-10=6\\p=\frac{6}{2}=3[/tex]
2 - Solving for t
[tex]-3(t+1)=18\\-3t-3=18\\-3t=18+3=21\\t=\frac{21}{-3}=-7[/tex]
3 - Solving for x
[tex]-\frac{2}{5}(x-10)=-10\\-\frac{2}{5}x+\frac{2}{5} *10=-10\\-\frac{2}{5}x+4=-10 \\-\frac{2}{5}x=-10-4=-14\\-\frac{2}{5}x=-14\\x=\frac{-14}{\frac{-2}{5} }=14*\frac{5}{2}=35[/tex]
4 - Solving for x
[tex]\frac{2}{3}(x-10)=-2\\\\x-10=\frac{-2}{\frac{2}{3} }=-2*\frac{\\3}{2}\\\\x-10=-3\\x=-3+10\\x=7[/tex]
Have a nice day!